Case report: Misdiagnosis of accessory spleen in the left adrenal region as an adrenal tumour after splenectomy - Zou, Yuhua; Xie, Xiaojuan; Yan, Sheng; Wu, Gengqing; Liu, Quanliang (Frontiers in Surgery, 2022)
Background Adrenal tumours are common in urology and endocrinology, and the diagnosis of adrenal tumours were mainly depends on imaging diagnosis. Howerver, misdiagnosis can still occur for some adrenal space-occupying lesions without specific manifestations or abnormal biochemical indexes. Methods We report the case of a 55-year-old patient with a soft-tissue mass in the left adrenal region, and have no specific manifestations or abnormalities in biochemical indexes. The patient had undergone open splenectomy 20 years ago for splenic rupture caused by traffic-accident trauma, and had a 10-year special history of hypertension. Because of the uncertain nature of the mass, surgical treatment was recommended. Results The surgeon managed to remove the left adrenal region mass. During the surgery, the adrenal source was excluded. In the histological examination, the splenic corpuscle and splenic medullary structure were seen under the microscope, and an accessory spleen was diagnosed. Conclusions The accessory spleen was located in the adrenal region rarely, and can easily be misdiagnosed as an adrenal tumour. When the cases show abnormal adrenal space-occupying lesions in imaging examinations, non-adrenal diseases should be considered. we need to combine different imaging techniques for analysis, and think more about it, avoid misdiagnosis leading to unnecessary surgery.